An introduction to economic evaluation in occupational therapy: cost-effectiveness of pre-discharge home visits after stroke (HOVIS) - Sampson, Christopher James; James, Marilyn; Whitehead, Phillip; Drummond, Avril E.R. (SAGE, 2014)
Introduction: Occupational therapy interventions, such as home visits, have been identified as being resource-intensive, but cost-effectiveness analyses are rarely, if ever, carried out. We sought to estimate the cost-effectiveness of occupational therapy home visits after stroke, as part of a feasibility study, and to demonstrate the value and methods of economic evaluation.